The effect of HIV educational interventions on HIV-related knowledge, condom use, and HIV incidence in sub-Saharan Africa: a systematic review and meta-analysis - Lena Faust; Sanni Yaya (BMC, 2018)
Abstract Background As high stigmatization of HIV and relatively low knowledge of HIV transmission and prevention measures persist in Sub-Saharan Africa, the improvement of HIV-related knowledge, and the evaluation of which types of interventions are most effective in this regard, is an important aspect of further prevention efforts. In addition, it is of interest to assess whether improvements in HIV-related knowledge may actually lead to increased engagement in preventive behaviours and ultimately lower HIV transmission. This study therefore aims to systematically review and meta-analyse the evidence for the effect of HIV-related knowledge interventions on 1) the improvement of HIV-related knowledge, 2) subsequent risk reduction behaviour (condom use), 3) lower incidence of HIV infection. Methods A literature search was conducted using the Embase and Medline databases, returning 746 after duplicate removal. Following abstract and full-text screening, 36 studies were ultimately included in the final review. Meta-analyses were conducted in R, using random-effects models, for the HIV-related knowledge, condom use, and HIV incidence outcomes, where sufficient data were available. Results Interventions assessed in the reviewed studies varied, including computer-based interventions, mass media campaigns, and peer education interventions. The interventions were generally found to be effective at improving HIV-related knowledge in the target population, with 10 studies reporting improved knowledge of risk reduction through condom use in the intervention group (out of 11 studies reporting data for this outcome), with 6 reporting these differences as significant (p < 0.05). Regarding knowledge of transmission routes, studies assessing peer education interventions often reported significant improvements in the intervention group. Meta-analysis results showed significantly higher odds among the intervention groups of correct knowledge of: risk reduction through condom use (OR: 3.09, 95%CI: 1.83-5.22, p < 0.0001), sexual transmission of HIV (OR: 5.86, 95%CI: 2.65-12.97, p < 0.001) and transmission through sharps (OR: 4.35, 95%CI = 3.21-5.90, p < 0.001), but non-significantly lower odds of HIV infection (OR: 0.97, 95%CI: 0.66-1.41, p = 0.854). Conclusion Peer-education-based interventions appear to be particularly effective in facilitating the uptake of HIV-related knowledge, particularly pertaining to transmission routes. There is some evidence that improved knowledge of HIV transmission and prevention facilitates increased subsequent engagement in preventive measures, although this requires further exploration. Trial registration PROSPERO Number: CRD42018090600